Impact of Immune Checkpoint Inhibitors on COVID-19 Severity in Patients with Cancer. (19th February 2022) - Tan, Ruoding; Yun, Cindy; Seetasith, Arpamas; Sheinson, Daniel; Walls, Robert; Ngwa, Innocent; Reddy, Josina C; Zhang, Qing; Secrest, Matthew H; Lambert, Peter; Sarsour, Khaled
Abstract: Background: Amid continued uncertainty about the management of cancer patients during the pandemic, this study sought to obtain real-world data on the use of immune checkpoint inhibitors (ICIs) before COVID-19 diagnosis and its association with severity and survival outcomes in cancer patients who contracted COVID-19. Methods: Cancer patients diagnosed with COVID-19 were identified from a large electronic health record database; those treated with ICIs before COVID-19+ diagnosis were matched in a 1:2 ratio to those not treated with ICIs, using a 2-step matching procedure. A descriptive analysis examined the difference in COVID-19 mortality (30-day and overall) and severity outcomes between the 2 cohorts, and overall survival was compared. Results: Among 17 545 adults ≥18 years with cancer who tested positive for COVID-19 between February 20, 2020, and January 28, 2021, in the US, 228 ICI-treated patients were matched to 456 non-ICI-treated patients, comprising the 2 study cohorts. Clinical characteristics differed significantly between the 2 cohorts before matching, with metastatic disease, lung cancer, a history of smoking, and the presence of pulmonary comorbidities being more common in the ICI-treated cohort; after matching, the 2 cohorts were similar. There were no significant differences between the ICI-treated and non-ICI-treated cohorts for 30-day mortality (12.7% vs. 14.9%, P = .235), overall mortality (22.4% vs. 22.4%, P = 1.000), hospitalization (38.6% vs. 39.0%, P = .912), or emergency department visits (16.7% vs. 14.7%, P = .500). Overall survival was similar between the 2 cohorts. Conclusion: This analysis adds to the clinical evidence base that use of ICIs before SARS-CoV-2 infection does not affect COVID-19 severity or survival outcomes, supporting the continued use of ICIs in cancer patients during the pandemic. Abstract : At the intersection of COVID-19 and cancer lies a population vulnerable to infection because of underlying disease and possible immunosuppression. This article examines whether cancer patients receiving immune checkpoint inhibitors (ICIs) were at greater risk of severe COVID-19 outcomes than cancer patients who were not receiving ICIs.